Sarcopenia and Postoperative Complication Risk in Gastrointestinal Surgical Oncology: A Meta-analysis. Issue 1 (July 2018) - Simonsen, Casper; de Heer, Pieter; Bjerre, Eik D.; Suetta, Charlotte; Hojman, Pernille; Pedersen, Bente K.; Svendsen, Lars B.; Christensen, Jesper F.
Abstract : Objective: The aim of the study was to evaluate sarcopenia as a predictor of postoperative risk of major and total complications after surgery for gastrointestinal cancer. Background: Sarcopenia is associated with poor survival in gastrointestinal cancer patients, but the role of sarcopenia as prognostic tool in surgical oncology has not been established, and no consensus exists regarding assessment and management of sarcopenic patients. Methods: We performed a systematic search for citations in EMBASE, Web of Science, and PubMed from 2004 to January 31, 2017. Random effects meta-analyses were used to estimate the pooled risk ratio for postoperative complications by Clavien-Dindo grade (total complications: grade ≥2; major complications: grade ≥3) in patients with sarcopenia versus patients without sarcopenia. Stratified analyses were performed by sarcopenia criteria, cutoff level, assessment methods, study quality, cancer diagnosis, and "Enhanced Recovery After Surgery" care. Results: Twenty-nine studies (n = 7176) were included with sarcopenia prevalence ranging between 12% and 78%. Preoperative incidence of sarcopenia was associated with increased risk of major complications (risk ratio 1.40; 95% confidence interval, 1.20–1.64; P < 0.001; I 2 = 52%) and total complications (risk ratio 1.35; 95% confidence interval, 1.12–1.61; P = 0.001; I 2 = 60%). Moderate heterogeneity was found for both meta-analyses. Subgroup analyses showed that sarcopenia remained a consistent risk factor across stratification by sarcopenia criteria, assessment methods, study quality, and diagnoses. Conclusions: Sarcopenia was associated with an increased risk of complications after gastrointestinal tumor resection, but lack of methodological consensus hampers the interpretation and clinical utilization of these findings. Combining assessment of muscle mass with measures of physical function may increase the prognostic value and accuracy in preoperative risk stratification. Abstract : Supplemental Digital Content is available in the text